The Influences of Small Side Games on The Results of Passing Accurary in Football at Football Academy HW Temanggung KU 12 - Lika Fauziyah; Agung Wahyudi (Universitas Negeri Semarang, 2026)
Football is a globally popular sport that demands high physical strength, strategy, and technical mastery, particularly in the fundamental skill of passing. At Football Academy HW Temanggung KU-12, initial observations revealed that many young players experienced tactical confusion and technical weaknesses, such as undirected passing and poor ball possession. These issues were largely attributed to static and monotonous training methods that failed to simulate real match conditions. This study aimed to analyze the influence of the Small Side Games (SSG) method on improving football passing accuracy among players in the U-12 category. This research employed a quantitative approach with an experimental pretest-posttest design. The study population consisted of 20 players from Football Academy HW Temanggung KU-12. Data were collected through a standard passing accuracy test before and after a 16-session treatment involving 3 vs 3 to 5 vs 5 game modifications. Data analysis included normality and homogeneity tests, followed by a Paired Sample T-Test to evaluate performance changes.The findings demonstrated a measurable increase in performance, with the average passing accuracy score rising from 17.70 in the pretest to 21.50 in the posttest. Statistical validation showed a calculated T-value of 7.933, which exceeded the T-table value of 1.729, supported by a P-value of 0.000. This intervention resulted in a total percentage increase in passing accuracy of 21.46%. Based on the results, it is concluded that the Small Side Games method provides a substantial boost to the technical proficiency of young athletes. The SSG approach creates a dynamic and contextual environment that allows players to touch the ball more frequently and make quicker decisions. This method is a highly effective tool for coaches to resolve tactical coordination weaknesses and accelerate the development of motor skills in early-age football players.